Incidencia del software educativo en el logro de aprendizaje significativo de los estudiantes del tercer año de bachillerato especialización administración de sistemas en la Unidad Educativa Santa Rosa de la ciudad de Santa Rosa provincia de El Oro, periodo lectivo 2013-2014. - Carrillo Jimenez, Diana Elisa (2014)
This research work has been developed according to research based on reality and using educational research methods and direct and indirect observation, which enabled investigate incidence of educational software in achieving meaningful learning applied specifically to high school students del Tercero de Bachillerato major in Management Systems de la Unidad Educativa Santa Rosa of the City of Santa Rosa, Provincia de El Oro, Teaching period 2013-2014. We sought to establish appropriate teaching methodologies for the use and correct application of educational software in the educational process also identify conditions of equipment for the implementation of computer software for the improvement and development of meaningful learning to the students. By the problems previously exposed such as the low technological academic level of the teachers, inapposite methodologies, equipment and inefficient infrastructure, which interfere with the achievement raised. The deficiency of updated knowledge produce continuing implementation traditionalists methods aside technological methodology, besides the low resources in the Institution cause an inefficient implementation of technological, generating a outdated technological learning. By implementing educational software we would achieve a high level of contribution to meaningful learning, because it facilitates the student-teacher interaction, allowing improving academic performance of students because the methodologies used by teachers are based on technological learning resources, strengthening meaningful learning in academic activities, due to the impact generated by the technology in education also implementing educational software contributes significantly in the teaching process, because it can raise levels of creativity, participation and production of new knowledge, strengthening the development of skills of student performance.